A first Namibian portfolio for languages (Journal for Studies in Humanities and Social Sciences, 2014)
Since its early beginnings in the 1970’s, the communicative approach has established itself as the preferred approach in the teaching and learning of French as a Foreign Language. It has signifi cantly changed teaching and learning methods by introducing innovative concepts, notions and material – such as communicative and intercultural competence, needs analysis, authentic material, and learner-centred practices. The assessment dimension had its share of transformation especially with the introduction of learners’ selfassessment and self-awareness skills. To operationalise these new self-assessment skills, innovative tools have been developed and tested. The Portfolio for Languages (a document produced by the European Council after the publication of the Common European Framework of Reference for Languages in 2001, which is now used in more than 38 countries in Europe) has proven its usefulness (for the learner as well as for the teacher) in the development of self-assessment skills, and in the monitoring an individual’s language development and of understanding learning objectives. To date no African portfolio for languages is in existence. In 2010, a team of fi ve Namibian teachers of French conceived the fi rst Namibian Portfolio for Languages that will be implemented in 2013 for all Grade 8 learners taking French as a Foreign Language in Namibian secondary schools. This pilot project will be carried out until 2017. The project is aimed at testing the eff ectiveness of the portfolio as an instrument if considered as a complementary tool to provide in the communicative approach needs in the Namibian context.